Blue Electrogenerated Chemiluminescence from Water‐Soluble Iridium Complexes Containing Sulfonated Phenylpyridine or Tetraethylene Glycol Derivatized Triazolylpyridine Ligands. Issue 42 (3rd September 2015) - Kerr, Emily; Doeven, Egan H.; Barbante, Gregory J.; Connell, Timothy U.; Donnelly, Paul S.; Wilson, David J. D.; Ashton, Trent D.; Pfeffer, Frederick M.; Francis, Paul S.
Abstract Incorporating phenylpyridine‐ and triazolylpyridine‐based ligands decorated with methylsulfonate or tetraethylene glycol (TEG) groups, a series of iridium(III) complexes has been created for green and blue electrogenerated chemiluminescence under analytically useful aqueous conditions, with tri‐n‐propylamine as a coreactant. The relative electrochemiluminescence (ECL) intensities of the complexes were dependent on the sensitivity of the photodetector over the wavelength range and the pulse time of the applied electrochemical potential. In terms of the integrated area of corrected ECL spectra, with a pulse time of 0.5 s, the intensities of the IrIII complexes were between 18 and 102 % that of [Ru(bpy)3]2+ (bpy=2, 2′‐bipyridine). However, when the intensities were measured with a typical bialkali photomultiplier tube, the signal of the most effective blue emitter, [Ir(df‐ppy)2(pt‐TEG)]+ (df‐ppy=2‐(2, 4‐difluorophenyl)pyridine anion, pt‐TEG=1‐(2‐(2‐(2‐(2‐hydroxyethoxy)ethoxy)ethoxy)ethyl)‐4‐(2‐pyridyl)‐1, 2, 3‐triazole), was over 1200 % that of the orange–red emitter [Ru(bpy)3]2+. A combined experimental and theoretical investigation of the electrochemical and spectroscopic properties of the IrIII complexes indicated that the greater intensity from [Ir(df‐ppy)2(pt‐TEG)]+ relative to those of the other IrIII complexes resulted from a combination of many factors, rather than being significantly favored in one area.